KEABSAHAN DAN AKIBAT HUKUM PERKAWINAN POLIGAMI YANG TIDAK MEMENUHI SYARAT ALTERNATIF (Analisis Penetapan Nomor 682/Pdt.P/2016/Pn.Dps) - I Gede Yudi Arsawan; Akhmad Budi Cahyono (Fakultas Hukum Universitas Muhammadiyah Palu, 2021)
ABSTRACT Marriage is the beginning of a new life for a person, because since there is an agreement between two individuals to marry, there is a change in the roles and responsibilities towards oneself, their partner, and their environment. Even though the Law of the Republic of Indonesia Number 1 of 1974 concerning Marriage adheres to the principle of monogamy, cases can occur where marriages occur in a polygamous manner, but to carry out a polygamous marriage, the conditions that must be met at least consist of 1 (one) alternative and 3 (three) conditions. cumulative conditions. However, there are cases where in the Denpasar District Court Decision Number 682/Pdt.P/2016/PN a husband is given permission by the Panel of Judges to practice polygamy even though there are no alternative requirements for a polygamous marriage to be fulfilled. Keywords: Marriage, Polygamy, Legal Terms of Marriage